Representasi Politik Opini Publik terhadap Pemilukada Sumatra Barat 2010 pada Koran Singgalang dan Program Sumbar Satu - Muhammad Thaufan A (Jurnal Komunikasi, 2014)
This paper aims to discover political representation of the local media namely Harian Singgalang regarding public opinion during the election in West Sumatra Indonesia. Furthermore, the complexity of media power will be discussed through such television program and the newspaper`s headline and special report. By using case study approach and critical discourse analysis of Norman Fairclough in analyzing text, discursive practice, and socio-cultural practice, it can be noted that political public opinion had been fully articulated in such local media representing collaboration actors and institution among media, politicians and local people.Political opinion could be sensed in the program “Menuju Sumbar Satu Padang TV” and located in the headlines and special report of Harian Singgalang during April-August 2010. Representation of political opinion in both Padang TV and Singgalang indicated media logic and also vested interested among such media and elites in order to maintain local democracy by spreading politically strategic information, persuading the audience, making the myth of good impression in order to win the election. Menuju Sumbar Satu Padang TV has depicted campaign strategy of some governors candidates while headlines and special report of Singgalang have extremely covered all candidates and transformed those dynamic public sphere for political consensus among media, politicians and the audience in promoting local democracy in West Sumatra 2010.